2008
DOI: 10.1302/0301-620x.90b5.20360
|View full text |Cite
|
Sign up to set email alerts
|

Autologous chondrocyte implantation in a novel alginate-agarose hydrogel

Abstract: Autologous chondrocyte implantation is an established method of treatment for symptomatic articular defects of cartilage. CARTIPATCH is a monolayer-expanded cartilage cell product which is combined with a novel hydrogel to improve cell phenotypic stability and ease of surgical handling. Our aim in this prospective, multicentre study on 17 patients was to investigate the clinical, radiological, arthroscopic and histological outcome at a minimum follow-up of two years after the implantation of autologous chondro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
172
3
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(183 citation statements)
references
References 24 publications
6
172
3
2
Order By: Relevance
“…15 Similarly, 10 years after second-generation ACI in 23 patients, the mean subjective IKDC score was 76.4. 16 However, the mean subjective IKDC score improvement in our study was smaller than that reported previously by Selmi et al 7 with the same procedure (31.7 and 40.8, respectively), which was similar to the improvement in our mosaicplasty group (44.3).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…15 Similarly, 10 years after second-generation ACI in 23 patients, the mean subjective IKDC score was 76.4. 16 However, the mean subjective IKDC score improvement in our study was smaller than that reported previously by Selmi et al 7 with the same procedure (31.7 and 40.8, respectively), which was similar to the improvement in our mosaicplasty group (44.3).…”
Section: Discussionsupporting
confidence: 77%
“…This easy-to-handle scaffold provides the cells with a three-dimensional environment, allowing them to develop into an osteochondral-like tissue. 7 In 2008, Selmi et al reported the 2-year outcomes of 17 patients managed using Cartipatch 1 showing significant improvements of the mean International Knee Documentation Committee (IKDC) score, O'Driscoll histological score and MRI analysis. 7 Those improvements were greatest in patients with cartilage defects larger than 3 cm 2 .…”
mentioning
confidence: 99%
“…Towards this end we theorized that a gel that can limit vascularization may favor hypoxia and hence chondrogenesis. In this study, we demonstrate that hyaline cartilage can be engineered de novo in the IVB by simply injecting agarose, a biocompatible (14,15) polysaccharide biomaterial that has no-inherent angiogenic properties (14,16,17) but promotes hypoxia (18). The engineered cartilage stains positive for collagen type-II and proteoglycans, is hypercellular, and is capable of remodeling within a full-thickness osteochondral defect with complete integration and does not undergo calcification even after 9 mo.…”
mentioning
confidence: 77%
“…Agarose has been used extensively in the tissueengineering studies of cartilage due to its ability to maintain chondrocytic phenotype in long-term suspension cultures [2,8,9,25]. Additionally, agarose is being used as a copolymer in autologous chondrocyte transplantation (Cartipatch 1 ; Banque de tissues, Mions, France) in Europe [39]. Our previous work demonstrates agarose can support the elaboration of functional cartilage in the chondral layer of bilayered tissue-engineered osteochondral constructs [28,36].…”
Section: Methodsmentioning
confidence: 99%